The Ethics and Politics of Environmental Cost-Benefit Analysis. - Nyborg, Karine (Routledge explorations in environmental economics., 2012)
Putting a price tag on the environment is controversial. The aim of this book is to discuss some of the ethical and political issues arising in the context of applied cost-benefit analysis and environmental valuation - and to do so using economic analysis, but in a language accessible to non-specialists. In particular, the author emphasizes the fundamental, but surprisingly often poorly understood distinction between normative and positive analysis, and the implications of this distinction for practical use of cost-benefit analyses.